Mutants of the Zebrafish K+ Channel Hcn2b Exhibit Epileptic-like Behaviors - Roberto Rodríguez-Ortiz (MDPI AG, 2021)
Epilepsy is a chronic neurological disorder that affects 50 million people worldwide. The most common form of epilepsy is idiopathic, where most of the genetic defects of this type of epilepsy occur in ion channels. Hyperpolarization-activated cyclic nucleotide-gated (HCN) channels are activated by membrane hyperpolarization, and are mainly expressed in the heart and central and peripheral nervous systems. In humans, four HCN genes have been described, and emergent clinical data shows that dysfunctional HCN channels are involved in epilepsy. Danio rerio has become a versatile organism to model a wide variety of diseases. In this work, we used CRISPR/Cas9 to generate hcn2b mutants in zebrafish, and characterized them molecularly and behaviorally. We obtained an hcn2b mutant allele with an 89 bp deletion that produced a premature stop codon. The mutant exhibited a high mortality rate in its life span, probably due to its sudden death. We did not detect heart malformations or important heart rate alterations. Absence seizures and moderate seizures were observed in response to light. These seizures rarely caused instant death. The results show that mutations in the Hcn2b channel are involved in epilepsy and provide evidence of the advantages of zebrafish to further our understanding of the pathogenesis of epilepsy.